The database tyranny. - Hogge, Becky (New Statesman, 2009)
In this article the author discusses the use of information technology by the British Labour Party government led by prime minister Gordon Brown. A number of issues are discussed including the legality of databases compiled by the government, aspects of maintaining database security and questions of privacy arising from information collection.